Short Communication: Antioxidant activity of ethanol extract of Chlorella sorokiniana cultured in tofu wastewater - HAMZA MURSANDI; DEVY SUSANTY; LANY NURHAYATI; ADE AYU OKSARI (Nusantara Bioscience, 2022)
Abstract. Mursandi H, Susanty D, Nurhayati L, Okasari AA. 2022. Short Communication: Antioxidant activity of ethanol extract of Chlorella sorokiniana cultured in tofu wastewater. Nusantara Bioscience 14: 155-159. Microalgae are microorganisms that grow quickly and produce secondary metabolites with antioxidant activity. Antioxidants of microalgae can be utilized in various aspects such as cosmetics, pharmaceuticals, supplements, and feed. Microalgae utilization will be more profitable if the microalgae can be cultured on waste media. This study aims to determine the concentration of a suitable medium for the growth of Chlorella sorokiniana Shihira & R.W.Krauss, total flavonoids, total phenolics, and the potential of ethanolic extract of C. sorokiniana as an antioxidant. This study cultured the microalgae C. sorokiniana on tofu liquid waste media at various concentrations (15, 20, 25, and 30%). The growth of C. sorokiniana on the media was observed using a spectrophotometer at 680 nm wavelength. C. sorokiniana biomass was collected on the 7th day. The biomass was extracted using ethanol as a solvent. Phytochemical analysis was performed using the standard method, Total phenolic content, total flavonoid content, and antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) were conducted to determine the IC50 value. The results showed that the best growth of C. sorokiniana was on TLW media at a concentration of 30%. The ethanolic extract of C. sorokiniana showed the presence of alkaloids, flavonoids, steroids, tannins, and saponins. The total phenolic content in the ethanolic extract of C. sorokiniana was 18.39 ± 0.29 mgGAE/g, and the total flavonoid content was 31.93 ± 5,60 mgQE/g. The IC50 of the ethanolic extract of C. sorokiniana was 288.95 mg/L, which shows this extract has a potent antioxidant.